Tax structure and tax evasion in Latin America - Gómez Sabaini, Juan Carlos (UN ECLAC SantiagoCL, 2012)
Studies the evolution and major features of the typical level and structure of the tax burden in the region over the last 20 years, identifies important differences between the countries and highlights the principal obstacles and constraints that most of the countries have encountered in attempting to increase their tax revenues and modify their tax structures.